False memory for context and true memory for context similarly activate the parahippocampal cortex. (June 2017) - Karanian, Jessica M.; Slotnick, Scott D.
Abstract: The role of the parahippocampal cortex is currently a topic of debate. One view posits that the parahippocampal cortex specifically processes spatial layouts and sensory details (i.e., the visual-spatial processing view ). In contrast, the other view posits that the parahippocampal cortex more generally processes spatial and non-spatial contexts (i.e., the general contextual processing view ). A large number of studies have found that true memories activate the parahippocampal cortex to a greater degree than false memories, which would appear to support the visual-spatial processing view as true memories are typically associated with greater visual-spatial detail than false memories. However, in previous studies, contextual details were also greater for true memories than false memories. Thus, such differential activity in the parahippocampal cortex may have reflected differences in contextual processing, which would challenge the visual-spatial processing view. In the present functional magnetic resonance imaging (fMRI) study, we employed a source memory paradigm to investigate the functional role of the parahippocampal cortex during true memory and false memory for contextual information to distinguish between the visual-spatial processing view and the general contextual processing view. During encoding, abstract shapes were presented to the left or right of fixation. During retrieval, old shapes were presented at fixation and participants indicated whether each shape was previously on the "left" or "right" followed by an "unsure", "sure", or "very sure" confidence rating. The conjunction of confident true memories for context and confident false memories for context produced activity in the parahippocampal cortex, which indicates that this region is associated with contextual processing. Furthermore, the direct contrast of true memory and false memory produced activity in the visual cortex but did not produce activity in the parahippocampal cortex. The present evidence suggests that the parahippocampal cortex is associated with general contextual processing rather than only being associated with visual-spatial processing.